SC29 Evaluation of medical student retention and transferability of clinical skills following simulation teaching. (November 2018) - Condron, Claire; Offiah, Gozie; Ekpotu, Lenin Patrick; Murphy, Siobhan; Kane, Daniel Kane
Abstract : Background: Inadequate clinical skills are a significant problem of present day medical education. 1 Simulation Based Education (SBE) is playing an increasingly important role in healthcare training worldwide to teach invasive procedures. This works aims to evaluate the retention levels of procedural skills taught and assessed by SBE and what re-training is required to restore decayed performance. This study also investigates how skilled performance decays over time and whether certain dimensions of clinical skills are more likely to decay. Summary of education programme: A mastery learning approach, using SBE, was employed to teach clinical skills to 3rd and 4th year medical students. Pre course video/procedural guides are provided online asynchronously which students can repeatedly access. 7 skills were taught over 2 years using task trainers. Following a demonstration, students practiced in small groups with tutor facilitated supervision and peer support prior to formal testing. Score sheets with itemised procedure checklists detailing the minimum passing standard (MPS) for each skill were used for assessment. The program provides the necessary educational experiences for self-directed repetitive clinical skill practice that is required to reach competency and remediation when necessary. Unannounced tests to demonstrate proficiency in the skills were completed in the final year by 51 students. Results: 55% of the students were deficit in 3 or more skills and 4% were not competent in 5 or more skills. Students were asked by questionnaire how many times and where they had practiced/performed the techniques. A significant number had never practiced some skills. A relationship was noted with the number of time students self-declared that they had practiced and their performance. Discussion, conclusions and recommendations: This study attempts to define what procedural skill performance look like at fixed periods of time elapse in an undergraduate medical program. Decay is evident in both psycho-motor and cognitive domains of the skills. Deliberate practice of clinical skills, under supervision of an engaged instructor, is a key component of the mastery model. 2 Experiences and assessments in the clinical setting need to be augmented with particular focus on direct observation and focused feedback to reinforce the skills acquired in the simulated setting. References: Birdane A, Yazici HU, Aydar Y, et al. Effectiveness of cardiac simulator on the acquirement of cardiac auscultatory skills of medical students. Adv Clin Exp Med2012;21(6):791–8. Ericsson KA. Deliberate practice and the acquisition and maintenance of expert performance in medicine and related domains. Acad Med2004;79(suppl 10):S70–S81.